Factors associated with caregiver compliance to an HIV disclosure intervention and its effect on HIV and mental health outcomes among children living with HIV: post-hoc instrumental variable-based analysis of a cluster randomized trial in Eldoret, Kenya - Magill, Elizabeth B.; Nyandiko, Winstone; Baum, Aaron; Aluoch, Josephine; Chory, Ashley; Ashimoshi, Celestine; Lidweye, Janet; Njoroge, Tabitha; Sang, Festus; Nyagaya, Jack; Scanlon, Michael; Hogan, Joseph; et al. (Frontiers in Public Health, 2023)
Background The HADITHI study is a cluster-randomized trial of children living with HIV and their caregivers in Kenya that aimed to increase rates of caregiver disclosure of their child's HIV status, encourage earlier status disclosure, and improve pediatric mental health and HIV outcomes. This analysis identified characteristics predicting caregiver non-responsiveness and compared outcomes among children based on disclosure status. Methods A penalized logistic regression model with lasso regularization identified the most important predictors of disclosure. The two-stage least squares instrumental variable approach was used to assess outcomes accounting for non-compliance to disclosure. Results Caregiver non-isolation and shorter time on antiretroviral therapy were predictive of HIV status disclosure. There were no statistically significant differences found in CD4 percentage, depression status, or mental and emotional status based on disclosure status up to 24 months-post intervention. Conclusion These findings have implications for specialists seeking to tailor disclosure interventions to improve caregiver-child dyad responsiveness.